Intravitreal Injection of Triamcinolone Acetonide for Diabetic Macular Edema - Muhammad Afzal Pechuho, Shahid Jamal Siddiqui, Syed Imtiaz Ali Shah (Pakistan Journal of Ophthalmology, 2009)
Purpose: To determine the clinical outcome of an Intravitreal Injection of Triamcinolone Acetonide in the treatment of Diabetic Macular Edema. Material and Methods: The Study included 16 patients (32 eyes) who were diagnosed with clinical significant macular edema and treated with laser photocoagulation both grid and focal, received intravitreal triamcinolone acetonide injection 4mg/0.1ml under topical anaesthesia. The visual acuity was recorded before and after injection with 1 to 3 months of followup. Applanation tonometery was performed and readings recorded before and after injection. Results: In this prospective study of 16 patients (32 eyes) with clinical significant macular edema (CSME) unresponsive to laser photocoagulation 11 patients were male (68.75%) and 5 female (31.25%) from 35 to 62 years of age, average age 52.25 years. Visual outcome after laser photocoagulation remained same in 19 eyes (59.37%), improved in 6 eyes (18.75%) and decreased in 7 eyes (21.87%). Visual outcome after intravitreal injection of triamcinolone acetonide improved in 18 eyes (56.25%) and remained same in 14 eyes (43.75%). Conclusion: Intravitreal injection of 4mg/0.1ml triamcinolone acetonide may be beneficial for improving vision in patients with clinical significant macular edema (CSME) who are unresponsive to conventional laser photocoagulation.